2019
DOI: 10.1029/2018gl081095
|View full text |Cite
|
Sign up to set email alerts
|

High‐Resolution Mapping of Nitrogen Dioxide With TROPOMI: First Results and Validation Over the Canadian Oil Sands

Abstract: TROPOspheric Monitoring Instrument (TROPOMI), on‐board the Sentinel‐5 Precurser satellite, is a nadir‐viewing spectrometer measuring reflected sunlight in the ultraviolet, visible, near‐infrared, and shortwave infrared. From these spectra several important air quality and climate‐related atmospheric constituents are retrieved, including nitrogen dioxide (NO2) at unprecedented spatial resolution from a satellite platform. We present the first retrievals of TROPOMI NO2 over the Canadian Oil Sands, contrasting th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

13
220
2

Year Published

2019
2019
2021
2021

Publication Types

Select...
6
4

Relationship

3
7

Authors

Journals

citations
Cited by 267 publications
(252 citation statements)
references
References 60 publications
13
220
2
Order By: Relevance
“…Anthropogenic emissions are driven by the 2011 National Emissions Inventory (NEI), scaled to model years by the Environmental Protection Agency annual total emissions (EPA and OAR, 2015). The Model of Emissions of Gases and Aerosol from Nature (MEGAN; Guenther et al, 2006) is used for biogenic emissions. The chemical mechanism is version 2 of the Regional Atmospheric Chemistry Mechanism (RACM2; Goliff et al, 2013) with updates from Browne et al (2014) and Schwantes et al (2015).…”
Section: Model Descriptionmentioning
confidence: 99%
“…Anthropogenic emissions are driven by the 2011 National Emissions Inventory (NEI), scaled to model years by the Environmental Protection Agency annual total emissions (EPA and OAR, 2015). The Model of Emissions of Gases and Aerosol from Nature (MEGAN; Guenther et al, 2006) is used for biogenic emissions. The chemical mechanism is version 2 of the Regional Atmospheric Chemistry Mechanism (RACM2; Goliff et al, 2013) with updates from Browne et al (2014) and Schwantes et al (2015).…”
Section: Model Descriptionmentioning
confidence: 99%
“…Previous analyses estimated regional CO 2 emissions based on satellite-derived NO x emissions and the NO x to CO 2 emission ratios from bottom-up emission inventories (Berezin et al, 2013;Konovalov et al, 2016;Goldberg et al, 2019b) or co-located satellite retrievals of CO 2 and NO 2 (Reuter et al, 2014). Hakkarainen et al (2016) confirmed the spatial correlation between CO 2 spatial anomalies and OMI NO 2 VCD enhancements at the regional scale using satellite observations at higher resolution. Hakkarainen et al (2019) also showed how overlapping OCO-2 CO 2 data and data of NO 2 from the recently launched (October 2017) European Union Copernicus Sentinel-5 precursor TROPOspheric Monitoring Instrument (TROPOMI; Veefkind et al, 2012) can be used to identify small-scale anthropogenic CO 2 signatures.…”
Section: Introductionmentioning
confidence: 61%
“…The tropospheric NO 2 VCDs retrieved from EMI spectra are first validated against the OMI QA4ECV NO 2 products and the operational TROPOMI NO 2 products 23 . EMI measurements are compared to the OMI and TROPOMI products due to their similar instrument characteristics, i.e., the push-broom design, spectral bands, and near-noon overpass time at~13:30.…”
Section: Discussionmentioning
confidence: 99%